Myocardial remodeling and arterial stiffness depending on aldosterone level in patients with chronic kidney disease and arterial hypertension - O. V. Kuryata; V. V. Semenov (Patologìâ)
The aim. To analyze the relationship between serum aldosterone levels and myocardial remodeling and changes in elastic properties of arteries in patients with chronic kidney disease (CKD) and hypertension (AH).